A molecular tool to assess the pathological relevance of alpha-globin DNA variants - Qadah, T.; Finlayson, J.; Newbound, C.; Pell, N.; Jennens, M.; Holmes, P.; Grey, D.; Beilby, J.; Ghassemifar, Reza (2012)
Aim: While the phenotype for heterozygous beta-thalassaemia is straightforward, it is more difficult to confirm a causative relationship for mutations in the alpha-globin genes. The aim of this study was to generate an in vitro system to evaluate the pathological relevance of α-globin mutations. Methods: The novel variant HBA1:c.301-3C>G was used as a model. In silico analysis predicted an aberrant acceptor splice site in the mutant sequence. Subsequent in vitro studies included generation of and transfection of an expression vector carrying the HBA1:c.301-3C>G mutation, RNA purification, reverse-transcription polymerase chain reaction (RT-PCR) and cDNA sequencing. Immunofluorochemistry (IFC) with antibodies specific to the N- and or C- terminal of the α-globin protein was used in protein detection. Results: In vitro molecular characterisation of this point mutation confirmed the preferential utilisation of a cryptic splice site at intron 2 of the pre-mRNA, resulting in a shift in the reading frame causing a premature termination codon (PTC) at codons 101/102 and generation of a truncated protein. Conclusion: We have described here a molecular tool to study mutations that affect α-globin pre-mRNA splicing and translation. We confirm in silico predictions of the consequences of the HBA1:c.301-3C>G mutation, proving aberrant RNA splicing and the production of a truncated α-globin protein.